The Influence Of Transformational Leadership, Knowledge Sharing, And Academic Integrity On Lecturer Innovativeness - Irma Salamah; Moeins, Anoesyirwan; Yulizain, Yulizain (Publisher Cv. Inara, 2023)
The purpose of this study, is to test and analyze the factors that influence both partially and simultaneously on the innovativeness of lecturers at 6 First State Polytechnic Colleges in the Ministry of Research and Technology, using a questionnaire that has been tested for validity and reliability against 200 respondents, in a verification way carried out through the method and analysis of structural equation models (Structural Equation Modeling) using Lisrel V.8.80 software. The results of research and hypothesis testing show that transformational leadership, knowledge sharing, and academic integrity affect both partially and simultaneously on the innovativeness of lecturers with a contribution of 73%. Of the three variables, academic integrity has a more dominant influence compared to other variables.